Selecting Therapeutic Targets in Inflammatory Bowel Disease (STRIDE): Determining Therapeutic Goals for Treat‐to‐Target. (September 2015) - Peyrin‐Biroulet, L; Sandborn, W; Sands, B E; Reinisch, W; Bemelman, W; Bryant, R V; D'Haens, G; Dotan, I; Dubinsky, M; Feagan, B; Fiorino, G; Gearry, R; et al.
Abstract : OBJECTIVES: The Selecting Therapeutic Targets in Inflammatory Bowel Disease (STRIDE) program was initiated by the International Organization for the Study of Inflammatory Bowel Diseases (IOIBD). It examined potential treatment targets for inflammatory bowel disease (IBD) to be used for a "treat‐to‐target" clinical management strategy using an evidence‐based expert consensus process. METHODS: A Steering Committee of 28 IBD specialists developed recommendations based on a systematic literature review and expert opinion. Consensus was gained if ≥75% of participants scored the recommendation as 7–10 on a 10‐point rating scale (where 10=agree completely). RESULTS: The group agreed upon 12 recommendations for ulcerative colitis (UC) and Crohn's disease (CD). The agreed target for UC was clinical/patient‐reported outcome (PRO) remission (defined as resolution of rectal bleeding and diarrhea/altered bowel habit) and endoscopic remission (defined as a Mayo endoscopic subscore of 0–1). Histological remission was considered as an adjunctive goal. Clinical/PRO remission was also agreed upon as a target for CD and defined as resolution of abdominal pain and diarrhea/altered bowel habit; and endoscopic remission, defined as resolution of ulceration at ileocolonoscopy, or resolution of findings of inflammation on cross‐sectional imaging in patients who cannot be adequately assessed with ileocolonoscopy. Biomarker remission (normal C‐reactive protein (CRP) and calprotectin) was considered as an adjunctive target. CONCLUSIONS: Evidence‐ and consensus‐based recommendations for selecting the goals for treat‐to‐target strategies in patients with IBD are made available. Prospective studies are needed to determine how these targets will change disease course and patients' quality of life.